Marimar (GMA, 2008)
The story of Marimar bespeaks a journey of a youg lass who has been deprived of everything that was rightfully hers. separated from her real parents at a young age. Marimar was found and raised by an old couple who treat her as their own grandchild. Not knowing that she is the sole heiress to riches of Don Gustavo Aldaba, Marimar lives a modest and carefree life by the sea. She befriends the ambitious Angelika, who later holds the greates grudge against her due to an incident that is beyong Mariamar's control.